IMPLEMENTASI MEDIA KARTON PADA MATA PELAJARAN MATEMATIKA DI KELAS V SEKOLAH DASAR NEGERI 02 MENSEMAT KECAMATAN SAJAD TAHUN PELAJARAN 2023-2024 - Neli Apriani, Eliyah, Sera Yuliantini (CV. ADIBA AISHA AMIRA, 2024)
This research was conducted because there was a problem that some of the class V students at Mensemat State Elementary School 02 tended to be inactive, learning was monotonous so that students felt disinterested, bored and sleepy when studying. Students do not like mathematics lessons, because they think that learning mathematics is difficult and scary for students, giving rise to a lazy attitude towards learning. By implementing this cardboard media, students are encouraged to be actively involved and increase understanding and make students enthusiastic in receiving learning material. The aim of this research is to determine the planning, implementation and implications of the fifth grade teacher in using cardboard media. This research uses a qualitative approach with a phenomenological type of research. The results of the research are planning, preparing a learning implementation plan (RPP), preparing teaching aids or media, paying attention to students' strengths and weaknesses. Implementation, conveying learning objectives, connecting the material that has been studied with the material that will be delivered, utilizing media and learning resources, conveying the steps and tasks that must be completed, asking several questions, drawing conclusions and giving a post-test. And the implications of media can attract students' attention, learning is more interactive, time is more efficient, the learning process can take place anytime and anywhere, and students' positive attitudes towards learning material and the learning process can be improved.